Technological Gap in Adoption of Pulse Crop Production - Pal, Mahesh; Singh, R. P.; Singh, Mamta (Indian Journal of Extension Education, 2014)
The technological gap between existing and recommended technologies of pulse crops was studied during 2011-12  among 50 respondents through Krishi Vigyan Kendra, Sant Kabir Nagar, Uttar Pradesh. It was found that a majority (56 %) of the farmers belonged to low technological gap category followed by medium (36 %) and high technological gap  (8 %) in the use of high yielding varieties (HYVs) of pulse crops. In case of seed rate, 60, 28 and 12 per cent of the farmers  belonged to low, medium and high technological gaps, respectively. In respect of seed treatment, a large proportion of  farmers (44 %) were found in high technological gap category and 46 per cent farmers had high technological gap in  method of sowing followed by medium (28 %) and low technological gap (26 %). The respondents were facing constraints  in terms of unavailability of quality seeds in time, high cost of seeds, heavy weed infestation, high incidence of diseases  and pests. Under socio-economic constraints, high cost of labour, high cost of inputs, unavailability of skilled labour in  time, lack of support price and lack of subsidy for inputs were expressed as constraints by 78, 70, 62, 52 and 44 per cent of  the respondents, respectively. Under technological constraints 66.00 per cent respondents also faced difficulties regarding  weak extension support, lack of conviction and awareness about technologies.
Keywords: Pulse crops; production technology; pulses scenario; technological gap; constraints